MODERNIZATION OF THE STRUCTURE OF SECTORAL ENERGY MARKETS UNDER THE CONDITIONS OF INTERNAL AND EXTERNAL CHALLENGES - PAVLOVA, Olena; PAVLOV, Konstantin; NOVOSAD, Oksana; SURIAK, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the issue of the organization of the functioning of energy sector markets. The main areas of activity of branch energy markets are specified. In our understanding, industry markets are systemic market formations of a specific type of activity, which function in a mesoeconomic environment and have a specific interaction of competitive relations and special pricing. The "structure-behavior-performance" methodology is applied, which allows for investigation of the essence of consequent modernization processes taking place in the world energy market with subsequent adaptation to the domestic energy industry. The essence of this model was to combine joint efforts between the market structure of the industry, which included a share of market power, with the corresponding market behavior of the subjects of a given market, which does not affect the general well-being formed in an independent environment. The implementation of the specified model is manifested in the fact that the variability of the world energy market affects the change in the market structure, volumes, and trends of demand and supply for certain types of energy and territorial differences. Resulting changes exert appropriate pressure on energy market subjects and generate cyclical economic development with subsequent adoption of tactical, strategic, short-term, and long-term decisions. Summarizing the conducted theoretical generalization of the activity of branch energy markets, it should be noted that the most optimal development model for Ukraine in the post-war period will be the model: "structure-behavior-performance," which will allow consolidation of the efforts of the main components of the country's energy system. In the future, processes of increasing the nationalization and regulation of sectoral energy markets will become inevitable and necessary for the state: natural gas, electricity, exploration, and extraction of RES. Special attention is paid to the processes of regulation of antimonopoly manifestations in sectoral energy markets, stimulation of low-carbon measures to increase the environmental nation of society and increase of requirements for energy security.
Keywords: energy market; industry; mesoeconomics; methodology; modernization; business entities; monopolization; state regulation